2002
DOI: 10.1046/j.1471-8286.2002.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers for the Mexican spotted owl (Strix occidentalis lucida)

Abstract: A genomic cosmid library was used to develop seven highly polymorphic microsatellite markers for the Mexican spotted owl (Strix occidentalis lucida). These are the first reported microsatellite markers derived from this species. The cloned and sequenced repeat motifs include a triplet repeat of (AAT)n, two tetranucleotide repeats of (GATA)n, a tetranucleotide repeat of (ATCC)n, a compound repeat of (GA)n(GATA)n and the two pentanucleotide repeats (AGAAT)n and (ATTTT)n. The microsatellites described represent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…Some of this variation among families is certainly a function of time and resources expended as hundreds of microsatellites have been identified in the agronomically important chicken (personal communication, H. Cheng, USDA East Lansing, MI, USA). However, other studies, comparable to ours have reaped substantially greater numbers of markers (Isaksson & Tegelstrom 2002;Korfanta et al 2002;Thode et al 2002). Only two studies have identified polymorphic microsatellite loci in Laridae (Given et al 2002;Tirard et al 2002).…”
Section: Discussionsupporting
confidence: 70%
“…Some of this variation among families is certainly a function of time and resources expended as hundreds of microsatellites have been identified in the agronomically important chicken (personal communication, H. Cheng, USDA East Lansing, MI, USA). However, other studies, comparable to ours have reaped substantially greater numbers of markers (Isaksson & Tegelstrom 2002;Korfanta et al 2002;Thode et al 2002). Only two studies have identified polymorphic microsatellite loci in Laridae (Given et al 2002;Tirard et al 2002).…”
Section: Discussionsupporting
confidence: 70%
“…All owls were genotyped at 10 variable microsatellite loci (Table 2) developed for Mexican spotted owls (S. o. lucida; loci: 6H8, 15A6, 13D8, 4E10.2; Thode et al 2002), Lanyu scops owls (Otus elegans botelensis; loci: Oe3-7, Oe053, Oe128, Oe129, Oe149; Hsu et al 2003Hsu et al , 2006, and ferruginous pygmy-owls (Glaucidium brasilianum; locus: FEPO5; Proudfoot et al 2005). One of these loci (Oe128) and an additional microsatellite marker (Bb126) are diagnostic of spotted versus barred owls (Funk et al 2007) and were genotyped to assure that no barred owls or spotted owlbarred owl hybrids were included.…”
Section: Samplingmentioning
confidence: 99%
“…Ten polymorphic microsatellite loci designed for pygmy-owls (Proudfoot et al 2005) and one locus (4E10.2) from the Mexican spotted owl (Thode et al 2002) were used to derive a genotype for each individual and to assess genetic variation within and between all populations. The 5¢-end of each forward primer was labeled with a fluorescent marker for genotyping on an ABI PRISM 377 automated DNA sequencer (Applied Biosystems, Foster City, California).…”
Section: Data Collectionmentioning
confidence: 99%
“…In this study, we examine patterns of genetic variation at 11 polymorphic microsatellite loci, 10 of which were isolated from the pygmy-owl (Proudfoot et al 2005) and one from the Mexican spotted owl (Strix occidentalis lucida, Thode et al 2002). Microsatellite markers exhibit high levels of genetic variation and have proven useful for detailed genetic studies within avian species (Barrowclough and Gutie´rrez 1990;Larson et al 2002;Pe´rez et al 2002;Csiki et al 2003).…”
Section: Introductionmentioning
confidence: 99%